Miscibility of chitosan-hydroxyethylcellulose blends in aqueous acetic acid solutions at 35 degrees C - Wali, A. C.; Naidu, B. V. K.; Mallikarjuna, N. N.; Sainkar, S. R.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2005)
The miscibility of blends of chitosan and hydroxyethylcellulose in a 2% acetic acid solution was studied by viscometry, densitometry, and refractometry at 35 degrees C. The data suggest that the blends were completely miscible in all proportions. Further, the membranes were fabricated from concentrated blend solutions. The solid-state compatibility of the blends was confirmed by scanning electron microscopy. (c) 2005 Wiley Periodicals, Inc.
Keywords: blends; miscibility; refractive index; viscosity